Micro-CT analysis of osteomyelitis of rabbit tibial for model establishment and biomaterials application in tissue engineering. Issue 12 (December 2022) - Li, Yufan; Chen, Li; Lin, Mingyue; Wang, Chenxin; Zhang, Rui; Li, Yubao; Zou, Qin
Abstract: Osteomyelitis is one of the most difficult diseases to treat in orthopedics field. The construction of animal models of osteomyelitis is now more mature but still lacks a deeper criterion other than "successful infection". In this work, rabbit tibial osteomyelitis model with S. aureus infection was established. Whole tibia, cortical bone around bone window, and tibial condyle were characterized in considerable detail using micro-CT and other means at 2/4/6 weeks, respectively. The results show that in addition to the obvious inflammatory response and bone destruction, osteomyelitis caused some other effects on compact and cancellous bone, and in particular, changes in bone mineral density after infection were of interest. Although the modeling groups all exhibited osteolysis and bone loss, their overall bone mineral density averages and those of the control groups were mostly in the range of 870 mg/cm 3 to 920 mg/cm 3, without statistical difference. The results suggest that overall bone mineral density is determined by both bone destruction conditions and the amount of dead bone deposition. This work provides a reference basis for the selection of time points for the subsequent animal models establishment and some valuable reference indicators of the application of biomaterials in tissue engineering. Abstract : Osteomyelitis; Animal model; Micro-CT; Bone tissue engineering.